Fenomena Perilaku Flexing terhadap Aktivitas Joging pada Generasi Z - Moh. Wahyuddin S. Adam; Abd. Rahman; Nurzazila Oka; Sri Rabiyanti Dai; Dwi Asfilawaty Bauna; Hapsa Musa (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The phenomenon of flexing, or showcasing achievements and lifestyle excessively on social media, has become an increasingly common trend among Generation Z. This study explores the relationship between self-esteem and flexing behavior, along with its impact on identity formation and mental health. Individuals with high self-esteem tend to share their accomplishments as a form of self-appreciation. However, without adequate emotional awareness and self-regulation, this behavior can escalate into narcissism and a dependence on external validation. Generation Z utilizes social media, especially Instagram, as a medium for self-expression, identity construction, and social recognition. In the context of jogging activities, posts on social media are not merely for showing off but serve as personal documentation, motivation, and inspiration for others. Jogging is not only viewed as a physical activity but also as a part of modern lifestyle and status symbol, often displayed through branded sportswear, smart devices, and aesthetic locations. Nevertheless, social pressure to maintain a certain image through social media can lead to psychological impacts such as identity crises, insecurity, and social stress. Previous research indicates that flexing behavior is driven by a desire for recognition, feelings of insecurity, obsession with others' possessions, and social pressure. Despite its negative sides, flexing also has potential positive effects, such as enhancing motivation to exercise, promoting healthy lifestyles, and strengthening supportive digital communities. Regular jogging has been proven to improve mental and physical health, including reducing anxiety and improving mood. Therefore, a healthy self-concept, emotional intelligence, and digital literacy are crucial for fostering responsible social media behavior. Generation Z must be equipped with critical awareness to distinguish between authentic self-expression and the illusion of recognition in today’s visually driven digital era.